The Internet in the field of Social Work: emerging forms of participation and socio-communitarian intervention - Arriazu Muñoz, Rubén; Fernández-Pacheco Sáez, José Luis (Cuadernos de Trabajo Social, 2013)
The Internet, in and of itself, constitutes a media that modifies and restructures the processes of interaction and socialization of an individual, group or society. The increasing use of online communication tools (Discussion Boards, LISTSERV email lists, IRC chats, etc.) has motivated, by their functionality, the redefinition of orthodox models of communication in space and time. By applying this concept to the field of Social Work, important questions arise, such as, Do these virtual tools of communication constitute an instrument with which to foment and invigorate socio-communitarian participation?, Could these tools be included within methodological proposals for intervention in the field of Social Work?, What role will the Internet, and more specifically, on-line tools of communication, play in Social Work in the coming decades? The objective of this paper is to address these questions globally and systematically, analyzing the advantages and disadvantages of the use of Information and Communication Technologies («ICTs») in the field of Social Work. We focus attention on the implications that technology has, and historically has had, for the processes of public participation and social intervention, reflecting on the potentiality of these tools for professional practice. We seek to definitively analyze the viability of these technological communication resources within the framework of professional competencies of Social Work.
Keywords: on-line social work; on-line communitarian participation; on-line tools of intervention; on-line volunteer service; Computer-Mediated Communication (CMC).